Diseño de un algoritmo inteligente para el aprendizaje de las operaciones matemáticas básicas en niños invidentes en el rango de edad de 6 a 9 años, por medio de una aplicación móvil lúdica. - Quinaucho Toapanta, Jhon Jairo (2023)
This research project focuses on design development of a mobile application aimedto improve learning of basic mathematical operations for blind children aged 6 to 9years old. To approach this research, different methods and techniques were used.Interviews to blind children and surveys with parents, both from the samespecialized schools, were implemented to obtain a holistic view of the experiencewith the application. The interviews revealed that mobile application contributedsignificantly to the blind children's learning and understanding of mathematicaloperations, as well as fostering their motivation and interest in the subject. Parentsalso showed positive perception and highlighted accessibility and autonomy itprovided to their children. The results of this research support effectiveness andrelevance of mobile application as an inclusive educational support tool for blindchildren in learning basic mathematics. With this information, which for futureimprovements and adaptations can be proposed to further benefit this group ofvisually impaired children. However, it is important to consider the limitations ofthe study and focus practical implications of findings obtained at the research.